2020
DOI: 10.34310/jskp.v7i2.393
|View full text |Cite
|
Sign up to set email alerts
|

Hubungan Kesejahteraan Spiritual dengan Kualitas Hidup pada Pasien Kanker Payudara di Poli Bedah RSUP Dr. M. Djamil Padang

Abstract: Di Indonesia peningkatan jumlah kasus baru serta jumlah kematian akibat kanker payudara terus meningkat. Situasi yang dialami pasien kanker payudara menyebabkan permasalahan meliputi perubahan secara fisik, fungsi sosial, psikis maupun spiritual seseorang dan ini mempengaruhi kualitas hidup pasien kanker payudara. Salah satu faktor yang mempengaruhi kualitas hidup pasien kanker payudara adalah kesejahteraan spiritual. Tujuan penelitian untuk mengetahui hubungan kesejahteraan spiritual dengan kualitas hidup pad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 1 publication
0
1
0
Order By: Relevance
“…The research findings indicate that the average anxiety level among patients is 80.78. Anxiety is an emotional condition characterized by fear without a clear source, involving worries about various aspects of life and deep, ongoing feelings of fear and worry (Hawari, 2016). Tania et al (2019) reported that the prevalence of anxiety levels among breast cancer patients was 92.5%, with 34.2% experiencing mild anxiety and 58.3% experiencing moderate to severe anxiety.…”
Section: Discussionmentioning
confidence: 99%
“…The research findings indicate that the average anxiety level among patients is 80.78. Anxiety is an emotional condition characterized by fear without a clear source, involving worries about various aspects of life and deep, ongoing feelings of fear and worry (Hawari, 2016). Tania et al (2019) reported that the prevalence of anxiety levels among breast cancer patients was 92.5%, with 34.2% experiencing mild anxiety and 58.3% experiencing moderate to severe anxiety.…”
Section: Discussionmentioning
confidence: 99%